Effect of Lysine Amino Acid in Artificial Feed Substituted with Moringa (Moringa oleifera L.) Leaves on Feed Efficiency of Bileh Fish Seeds (Rasbora sp.) - Vito, Bastian; Diansyah, Sufal; Islama, Dini; Samuki, Khairul (Universitas Teuku Umar, 2024)
This study aims to test the effectiveness of amino acid lysine in artificial feed in increasing feed efficiency of bileh fish fry (Rasbora sp.). The experimental design used was a non-factorial completely randomized design (CRD) with five treatments and three replications. The treatments included: feed without lysine (P0), feed with lysine 1.2%/kg (P1), 1.4%/kg (P2), 1.6%/kg (P3), and 1.8%/kg (P4). The fish fry used amounted to 10 fish per container with a size of 2 cm and a weight of 0.10 grams, reared for 40 days. The results of data analysis using ANOVA showed that the provision of amino acid lysine had a significant effect on specific growth rate, but no significant effect on survival, feed conversion ratio and feed efficiency.